Cutting force of end cutting tool milling machining - Sharifah Noor Shahirah, Syed Mohd Nordin (2007)
In end milling, depth of cut is one of the cutting parameter that affects the cutting forces. In this study, three components of the cutting forces developed during end milling AISI 1020 Mild Steel. However, this project are focusing more on cutting force at vertical direction(z-direction) seems that, the main reasons of this project is to study the effects of depth of cut on the cutting force besides to analyze the cutting force between 2-flute and 4-flute helical end mill. For the cutting force measurement, a Kistler Quartz 3-Component Dynamometer was used. Depending on the different depth of cut where value for spindle speed and feed rate are constant, the cutting forces were evaluated for the AISI 1020 Mild Steel. Within certain cutting parameters range, the increasing depth of cut increased the cutting forces. Beside that, cutting force requirement for 2-flute High Speed Steel helical end mill are higher compare to 4-flute High Speed Steel helical end mill.